Entrepreneurial attitudes and perceptions in a cross-country setting: evidence from GEM data - Fernandes, Paula O. (2014)
In the late 20th century, entrepreneurship re-emerged as a key outline item of economic policy makers across Europe, both for some na-tions as well as for European Union as a whole. Reasonable economic growth joined with constantly high levels of unemployment encouraged expectations of entrepreneurship’s potential as a source of job creation and economic growth. In spite of this growing interest, an inclusive theo-retical and empirical research is needed. This paper aims to identify groups of countries that share similar patterns regarding the characteristics of entrepreneurial attitudes and perceptions. For this objective, it was selected 54 countries from the 2009 GEM survey, and a k-means cluster analysis technique was used. The results show three clusters with different entrepreneurial attitudes among the countries - high, medium and low entrepreneurial attitudes and perceptions.